2019
DOI: 10.1155/2019/2916547
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Toxoplasma gondii to Ethanolic Extract of Tinospora crispa in Vero Cells

Abstract: Background Toxoplasmosis remains widely distributed globally and is one of the major neglected parasitic zoonotic infections. The infection is still endemic in most parts of the world due to poor control as well as challenges of the currently used medications which can be overcome by using natural products. This study evaluated the effect of ethanolic extract from the stem of Tinospora crispa (EETC) on host cell invasion and intracellular replication of Toxoplasma gondii. Method The stem powder of T. crispa wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
6
14
0
Order By: Relevance
“…Indeed, several medicinal plants have been reported in the traditional treatment of toxoplasmosis. Also, several pharmacological studies demonstrated the ability of medicinal plant extracts to inhibit in vitro and in vivo the growth of T. gondii [1,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several medicinal plants have been reported in the traditional treatment of toxoplasmosis. Also, several pharmacological studies demonstrated the ability of medicinal plant extracts to inhibit in vitro and in vivo the growth of T. gondii [1,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…11 The use of ethanol 99.9% showed also relatively lower yield (15.08 % (W/W)). 12 Another study using 70% ethanol indicated a yield which was 19.34 % (W/W). 13 Comparison to the yield from further fractionation processes such as n-hexane and water solvent showed that our result was relatively higher than the yield from n-hexane fractionation by Irianti and Warsinah that indicating 24.1 % (W/W) 9 and 22.06 % (W/W) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For the proliferation evaluation, the HFF‐1 cells were infected with tachyzoites for 1 h, then washed and treated for 24 h with the extracts (posttreatment). Once the infection hours were completed, the culture was washed gently three times with medium RPMI without foetal bovine serum (FBS) to eliminate extracellular parasites (Leesombun et al, 2016; Sharif et al, 2019). Finally, the cells were observed with a fluorescence microscope using an optical zoom (20×) and four photographs per field were taken.…”
Section: Methodsmentioning
confidence: 99%